Mutual Aid Groups for Loneliness, Psychosocial Disability, and Continuity of Care - Rojas-Andrade, R (SPRINGER, 2024)
The objective of the present study was to evaluate the effectiveness of mutual help groups in continuity of care, loneliness and psychosocial disability in a Colombian context. For this, a quasi-experimental design is used, with pre- and post-intervention assessments due to non-randomized participant allocation. The study involved 131 individuals with mental disorders. The Psychosocial Disability Scale, The Alberta Scale of Continuity of Services in Mental Health, the UCLA Scale and the Zarit Caregiver Burden Scale were employed. The intervention was based on the core components of mutual aid groups. Significant differences (p < 0.001) were observed for the study variables, particularly in Loneliness, Continuity of Care, and various domains of psychosocial disability. A large effect size was found for these variables after the intervention. Most variables exhibited a moderate to large effect. This study demonstrates the effectiveness of mutual groups facilitated by mental health personnel at the primary care level.